PENERAPAN SUMBER DAYA MANUSIA DAN SARANA PRASARANA TERHADAP PENINGKATAN MUTU MENGHAFAL AL-QUR’AN DI PP AL AZHAR - Faikotul Himah (IAIN Bone, 2021)
This study aims to determine how the application of human resources in improving the quality of memorizing the Qur’an in PP Al Azhar and knowing how to application of educational facilities and infrastructure in improving the quality of memorizing the Qur'an in PP Al Azhar. The research approach used descriptive qualitative, the data used were primary data from observations, interviews and documentation. The results showed that PP Al Azhar has carried out planning in managing human resources. Human resources were provided with predetermined job descriptions and provided trainings so that educators were able to understand how to create learning that was easy for students to understand in memorizing Al-Qur'an. PP Al Azhar conducted a needs analysis in planning infrastructure by involving a special team formed to conduct deliberations related to organizing or classifying goods, people, responsibilities of people and funds. Infrastructure facilities are carried out by scheduling their use. An inventory is carried out to control the presence and location of the infrastructure if they are used at any time. The quality of memorizing Al-Qur'an in the PP Al Azhar has increased after implementing human resources and infrastructure. This increase was manifested in various kinds of academic and non-academic achievements. The quality of memorizing Al-Qur'an in the PP Al Azhar has been proven to have increased with the presence of competent human resources and supporting infrastructure which is shown by the increasing number of students memorizing Al-Qur'an every day.